Premature ejaculation - current concepts in the management: A narrative review - Arkiath Veettil Raveendran; Ankur Agarwal (Shahid Sadoughi University of Medical Sciences, 2021)
Premature ejaculation (PE; early ejaculation or rapid ejaculation) is a common sexual problem affecting about 20-30% of men in the sexually active age group. PE can be of four types: Primary, secondary, natural variable, and subjective PE. Various non-pharmacological and pharmacological treatment options are available to treat PE including Dapoxetine, which is specifically developed for the treatment of PE. In this review, we discuss the pathophysiology and management aspects of PE.